PUBLIC SPEAKING VERSUS INTERPERSONAL COMMUNICATION IN UNIVERSITY SETTINGS - Sunarti, Erna (Esteem Journal of English Education Study Programme, 2025)
Effective communication is a cornerstone of academic and professional success, with both public speaking and interpersonal communication playing pivotal roles in university settings. This article examines the differences and interrelations between these two forms of communication within the context of higher education. Public speaking, characterized by structured, formal presentations, often highlights students’ ability to organize thoughts and present ideas to larger audiences. It is crucial for activities such as class presentations, conferences, and academic competitions. On the other hand, interpersonal communication, which involves more spontaneous, informal, and one-on-one or small group interactions, is essential for effective collaboration, networking, and fostering relationships in group projects and everyday university life. While public speaking develops clarity and persuasive skills, interpersonal communication fosters adaptability, empathy, and deeper connections. Both forms of communication are complementary and equally necessary for students’ holistic development, equipping them with the tools to thrive academically and in future professional environments. This article explores strategies to strengthen both public speaking and interpersonal communication skills, emphasizing the importance of integrating them into university curricula to prepare students for diverse communication challenges.